GREEN INFRASTRUCTURE AS NATURE-BASED SOLUTIONS FOR WATER RESOURCES MANAGEMENT IN INDONESIA - Maria Agnes; Muhammad Tayyab Naqash (Universitas Trisakti, 2025)
Law No. 17/2019 declared that the main objective of Indonesia’s national water resources management is one that is managed in a comprehensive, integrated, and environmentally conscious manner, with the purpose of establishing justice and the welfare for the people. Not only stating if the national water resources management must be environmentally conscious, but the law also defines conservation as one of the efforts required for water resources management. Thereby, in the interest of carrying out the formulation and implementation process of water resources management as defined by the law, currently the Directorate General of Water Resources has included water resources conservation as one of its thirteen general policies. Even so, these conservation and environmentally conscious efforts can be found in the operational strategies, goals and performance indicators. Aims: This study was aimed to obtain additional insights can be benefited for the formulation and implementation process in Indonesia. Methodology and results: Corresponding to the recent development in water resources management strategies which have begun to lead into the direction of nature-based solutions, or popularly also known as green infrastructure, this study conducts a literature review on the utilization of green infrastructure as water resources management strategies in several other countries. Conclusion, significance and impact study: Directorate General of Water Resources’ strategic planning document for the year 2020-2024 also indicates if the objective of Indonesia’s national water resources management is still focusing on grey infrastructure, particularly the construction of multipurpose dams.